Práticas de escrita de crianças do primeiro ciclo de alfabetização em situações reguladas pela professora e pelo grupo: em situações reguladas pela professora e pelo grupo - Claudia Starling Bosco (2010)
This research is focused on the writing practices of textual genres of the children from two different classes of a Municipal Educational School of Belo Horizonte, both at the first level of literacy, produced during exchanges controlled by the educators and by the group of children. The main objectives are: to examine how the textual genres are organized, composed, and spread in the school context; recognize if the children show any awareness of the textual genres; and wonder about what the children think about writing practices inside and outside the school. Structured from the designs of the qualitative research, this work is based on methodological procedures associated to the ethnographic perspective. It is constructed by the immersion of the researcher in the field, participant-observation, use of written diaries, and semi-structured interview as the most important instruments for data collection. The research is based on the studies of Bakhtin (2003), because they consider language as a social, historical and ideological phenomenon. In this sense, it is utilized Bakhtins concepts of individual as the one who is formed from the interaction with others discourses. The research dialogues with the notion of discourse genre, which makes possible to comprehend many uses of language in different social exchanges. It is also based on the studies of Ferreiro (1986) about Writing Production; Soares (1998) about Literacy; Costa Val (1991) and Geraldi (2002) about the Teaching of Writing; and Rojo (2001), Bazerman (2005), Dolz and Schneuwly (2004), and Marcuschi (2007) about Textual Genres. The research points towards the existence of a teaching of writing which differs from the real uses of language, but, on the other hand, it also confirms the existence of plenty of use of textual genres in authentic situations by the children during their moments of social interaction, though such practices are neither noticed by the educator nor by the children. It is also perceived a rich variety of knowledge shown by the children about the uses of textual genres within and outside the school. The results of this research have got direct implications towards the necessity of rethink the teaching of writing, in order to entail the textual genres perspective, and they also have got a wide range of possibilities to better comprehend the use of writing language for children during the literacy process.